The economics of additive manufacturing and topology optimisation – a case analysis of the electric scooter - Toshev, Rayko; Kolatsis, Nikos; Shamsuzzoha, Ahm; Helo, Petri (Taylor & Francis, 2023)
This article describes the process of topology optimisation (TO) of three components of an electric scooter, namely the neck, platform, and suspension bracket. We use these example parts to investigate the additive manufacturing (AM) workflow, from re-design to nesting and support approach that has an impact on the total costs and time required for product development and manufacturing, with a focus on Direct Metal Laser Sintering (DMLS) technology. Due to the mathematically generated shape, components that are topology optimised and fabricated through AM have improved structural load-to-weight ratio. The article elaborates on the cost of manufacturing these new geometrical structures and re-designing existing components. Recognising topology-optimised design features for the LPBF manufacturing process like creating touch points between parts in 3D nesting orientations and lattice structure integration reduces cost in volume production. Our study shows that it is beneficial for the DMLS process to perform finite element analysis (FEA) and optimise components using TO and lattice structures, as weight reduction also translates to cheaper fabricating parts. Defining and implementing a streamlined workflow for editing the complex automatically generated support structures improves manufacturability. Such approaches encourage companies to adopt wider LPBF processes in mainstream industries.
Keywords: Additive manufacturing; lattice structures; topology optimisation; direct metal laser sintering; finite element analysis; fi=Tuotantotalous|en=Industrial Management|